(untitled) (Journal of Nepal Geological Society, 2016)
This paper focuses on evolution of the fluvial system in the late Cenozoic Siwalik Group along the Kankai River section of East Nepal. The Siwalik Group lies on the southern flank of the Himalaya and composed of molasse sediments, which were derived from upheaval of the Himalaya. On the basis of lithology, assemblage of sedimentary structures and sediment body architectures, seven facies associations (FA1 to FA7) are recognized in the Kankai River section, East Nepal Himalaya. These recognized facies associations are closely related to each lithostratigraphic units of the area (Ulak 2009). The lower and upper members of the Lower Siwaliks are the products of the fine-grained meandering and flood flow-dominated meandering systems, respectively. The lower, middle and upper members of the Middle Siwaliks are interpreted as the deposits of the sandy meandering, deep sandy braided and shallow braided systems, respectively whereas the lower and upper members of the Upper Siwaliks are the products of the gravelly braided and debris flow-dominated braided systems, respectively. Paleohydrological characteristics and its evolutional changes of the group have been estimated by using grain diameter and thickness of fining upward fluvial successions. The paleohydrology suggests an increase in of flow velocity, channel slope gradient, and discharge of the fluvial system. Paleovelocity varies from 0.19 m/s to 5.31 m/s paleochannel gradient and paleodischarge changes from 6.67x10-5 to 2.97x10-4 m/m and 101 to 104 m3/s, respectively in stratigraphic upward. The progressively changes in the paleohydrology reflect the southward propagation of thrust activities, caused upheaval of the Himalaya.